Pedunculated poroma on forearm: A rare clinical presentation - Meeta D Mantri; Ameet Dandale; Rachita S Dhurat; Smita Ghate (Wolters Kluwer Medknow Publications, 2014)
Eccrine poroma (EP) is an adnexal tumor that commonly occurs on soles as a soft sessile flesh colored nodule. We report here a case of 54-year-old man who presented with a pedunculated red colored nodule on the right forearm. Histopathological examination was consistent with EP. This presentation of EP on the forearm as a pedunculated nodule is rare.